2015
DOI: 10.1016/j.tetasy.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective addition of aryl ketones and acetone to nitroalkenes organocatalyzed by carbamate-monoprotected cyclohexa-1,2-diamines

Abstract: Abstract-Enantiomerically pure carbamate-monoprotected trans-cyclohexane-1,2-diamines are used as chiral organocatalysts for the addition of aryl ketones and acetone to nitroalkenes leading to enantioenriched β-substituted γ-nitroketones. The reaction is performed in the presence of 3,4-dimethoxybenzoic acid as additive, in chloroform as solvent at room temperature, achieving enantioselectivities up to 96%. Theoretical calculations are used to justify the observed sense of the stereoinduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…A hydrogen bond interaction explained the stereochemical outcome achieved when catalyst 86 was used in the reaction of aryl methyl ketones with aryl and heteroaryl nitroolefins. In this case, computational studies showed that, in apolar solvents, the existence of the hydrogen bond explained the formation of the ( R )-Michael product in high enantioselectivities whereas in polar solvents the partial rupture of the H-bond activation induces the formation of the ( S )-product, explaining the loss of enantioselectivity [ 108 ].…”
Section: Carbon Nucleophilesmentioning
confidence: 99%
“…A hydrogen bond interaction explained the stereochemical outcome achieved when catalyst 86 was used in the reaction of aryl methyl ketones with aryl and heteroaryl nitroolefins. In this case, computational studies showed that, in apolar solvents, the existence of the hydrogen bond explained the formation of the ( R )-Michael product in high enantioselectivities whereas in polar solvents the partial rupture of the H-bond activation induces the formation of the ( S )-product, explaining the loss of enantioselectivity [ 108 ].…”
Section: Carbon Nucleophilesmentioning
confidence: 99%
“…Replacement of the fluorine atoms of the boron bridge by trifluoroacetoxy (2-O, 3-O and 4-O) or cyano (1-C, 2-C, 3-C and 4-C) groups was carried out by the reaction of F-aza-BODIPY with trimethylsilyl trifluoroacetate (TMSOCOCF 3 ) or trimethylsilyl cyanide (TMSCN), respectively, in the presence of AlCl 3 as Lewis acid in 18 to 79 % yield (see Experimental Section), according to the experimental procedure previously describe by our research group. [31]…”
Section: Synthesismentioning
confidence: 99%
“…In previous publications dealing with BODIPYs, we reported that their fluorescence response could be ameliorated by substituting the fluorine atoms at the boron bridge with electron withdrawing moieties like cyano and, especially, trifluoroacetoxy. [31] Against this background, we tested this strategy in the above described F-aza-BODIPYs and designed the corresponding C-and O-aza-BODIPYs to further optimize the fluorescence performance of the red-emitting dyes. The corresponding O-aza-BODIPY from compound 1-F could not be attained, since the product was chemically unstable and decomposed quickly.…”
Section: Chemical Modifications At the Boron Centre: C-and O-aza-bodipysmentioning
confidence: 99%
“…As one of the main classes of ketone compounds, γnitro ketones are widely used as intermediates for the synthesis of various functionalized carbocycles. [3][4][5][6][7][8] The reported typical synthetically viable procedures for the construction of γ -nitro ketones include: i) the conjugate addition of nitromethane to chalcone; [9][10][11][12][13] ii) the detrifluoroacetylative Michael addition of 1-trifluoromethyl-1,3-diketones to conjugated nitroalkenes; 14 iii) the amine-catalyzed Michael addition of ketones to nitrostyrene; [15][16][17][18][19][20][21][22][23][24][25] iv) the nickel-catalyzed decarboxylative Michael addition of β-ketoacids to nitrostyrenes 26,27 (Scheme 1). However, some drawbacks, such as low yield, limited diversity and expensive substrates, still remains in the existing methods.…”
Section: Introductionmentioning
confidence: 99%